Perancangan Perangkat Lunak Kehadiran Siswa Berbasis Smart QR Card di SMK Muhammadiyah 2 Palembang - Dicky Afriyansyah; Diana Diana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
In today's digital era, educational institutions require an information system that can facilitate the process of serving and managing student data quickly and efficiently. SMK Muhammadiyah 2 Palembang still manages student attendance data conventionally, thus requiring a web-based computerized system. This study aims to design and develop a web-based student attendance application using the Laravel framework and Smart QR Card technology. System development was carried out using the Agile Development method. This method allows the development of a system that is adaptive to user needs. The results of this study are a student attendance web application that can assist the process of attendance data collection, monitoring student attendance, managing class schedules, and attendance reports. System testing was carried out using the Blackbox Testing method to ensure functionality runs according to requirements. With this application, it is expected that the process of recording student attendance data at SMK Muhammadiyah 2 Palembang will be faster and more accurate.